New species of halenia from colombia and venezuela (1944)
Halenia phyllophora, sp, nov. / Halenia Garcia-Barrigae, sp. nov. / Halenia insignis, sp. nov. / Halenia nivalis, sp, nov. / Halenia venezuelensis, sp. nov.